Quantifying the Personal Income Tax Benefits of Backdating: A Canada – US Comparison - Compton, Ryan A.; Nicholls, Christopher C.; Sandler, Daniel; Tedds, Lindsay M. (Columbia Journal of Tax Law, 2012)
This paper contrasts the post-tax returns of backdated at-the-money options to currently-dated in-the-money options (with the same strike price as the backdated options) and demonstrates that a Canadian executive can earn a significantly larger after-tax return from backdated options compared to a US executive. We tie this to the favorable Canadian tax treatment of executive options relative to their treatment in the United States. The comparison suggests that the personal tax regime may have been one of the factors which impacted the desire to receive backdated options in lieu of other forms of compensation in Canada but not so in the United States.